A Comparative Study of Impact of NPA on Growth of Public and Co-operative Sector Banks in Amravati District - Ingale, Yogesh S; Harne, Arun G (Journal of Commerce and Trade, 2018)
Indian banking sector of having a serious problem due non performing. The financial reforms have helped largely to clean NPA was around Rs. 52,000 crores in the year 2004. The earning capacity and profitability of the bank are highly affected due to this NPA is defined as an advance for which interest or repayment of principal or both remain outstanding for a period of more than two quarters. The level of NPA act as an indicator showing the bankers credit risks and efficiency of allocation of resource. The rising incidence of NPAs has been generally attributed to the domestic economic slowdown. It is believed that with economic growth slowing down and rate of interest going up sharply, corporate have been finding it difficult to repay loans, and it has added up to rising NPAs. Classification-JEL : E59, G21, G28, G32.